FERTILITY IMPROVEMENT BY HORMONAL THERAPIES IN REPEAT BREEDING COWS - MORE, R M; PATIL, A D; KUMBHAR, U B; MUGALE, R R (The Indian Journal of Animal Reproduction, 2023)
The present experiment was under taken to study the efficacy of progesterone and GnRH in repeat breeding oeoni cows. Thirty two Deoni cows were selected and divided into four groups. Each group comprises eight animals. Group I cows were administered inj. Hydroxyprogesterone@250 mg on 5th day of artificial insemination, Group II cows were administered inj. GnRH@ 10 mcg at the time of artificial insemination, Group Ill cows were administered inj. GnRH@ 10 mcg on 5th day of artificial insemination and Group IV remains untreated served as control. The conception rate of groups I, II, Ill and IV was 50.00, 75.00, 62.50 and 25 per cent, respectively. The conception rate of group II was higher than that of group I and group Ill. Thus the study reveals that the administration of GnRH at the time of artificial insemination improves the conception rate in repeat breeder Deoni cows.